PARASITOLOGICAL SURVEY IN IKEI ISLAND, OKINAWA - ISEKI, MOTOHIRO; TAKADA, SUEHISA; UNI, SHIGEHIKO; YONEMOTO, SHINICHI; TANABE, KAZUYUKI; TAJIMA, ISAO; NISHIO, YASUYOSHI; SANO, RYUZO (Japanese Journal of Tropical Medicine and Hygiene, 1974)
The parasitological survey was made on the residents in Ikei Island of Okinawa in December 1972 and in July 1973. 1) For the fecal and perianal examination of intestinal helminthic parasites, the serophan thick smear method, the filter paper culture method and the pinworm adhesive serophan tape method were used. The parasite species and their positive cases found from stool and perianal samples examined in 1972 were Necator americanus 20 of 356 (5.6%), Strongyloides stercoralis 7 of 306 (2.3%), Enterobius vermicularis 26 of 283 (9.2%), Heterophyes sp. 3 of 319 (0.9%), Trichuris trichiura 1 of 319 (0.3%) and Hymenolepis nana 1 of 319 (0.3%), and those in 1973 were N. americanus 2 of 162 (1.2%), S. stercoralis 5 of 162 (3.1%), E. vermicularis 3 of 156 (1.9%), Heterophyes sp. 1 of 162 (0.6%) and T. trichiura 1 of 162 (0.6%) respectively. Necator and Strongyloides were found from adults, while pinworm was mainly from children, and Ascaris was not found at all in this Island. 2) For treatment of parasite positive cases in our survey, following anthelmintics were administered respectively; for hookworm disease 2 g as base of 1-brom-naphthol (2) twice a day for 2 days, for strongyloidiasis 5 mg/kg/day as base of pyrvinium pamoate suspension for 4 successive days and for oxyuriasis 5 mg/kg as base of pyrvinium pamoate in a single dose. One month after the treatment, 11 out of 14 cases of hookworm disease, 2 out of 4 cases of strongyloidiasis and 12 out of 17 cases of oxyuriasis became negative in the reexamination. 3) On the survey of filariasis, the 30 cmm thick blood smear method and the filarial skin test, with Sawada Antigen FST3 10 7., were carried out in July 1973. The positive cases of Microfilaria bancrofti were found from 11 of 272 cases examined (4.0%) and the mean number of microfilaria per 30 cmm blood samples (MFD) in positive cases was 13.3 microfilariae with highest density of 61 microfilariae. Among the positive cases, one has shown mild symptoms of acute filariasis but others were asymptomatic carriers. On the age of the carriers, one was 17 years old female and others were older than 42 years. The positive cases of skin test were found in 93 out of 192 cases examined (48.4%), and the high positive rates were revealed in young age group as well as in old age groups. 4) The mosquitoes collected during the survey in 1973 were adults of Armigeres subalbatus, Culex fatigans, Aedes albopictus and some Aedes togoi by light traps, and larvae of A. albopictus, A. togoi and some Toxorhynchtes sp. from breeding places of different kinds. 5) Hemagglutinating antibody for toxoplasma was examined with Hanaki-Nobuto's method in July 1973, and the positive cases (1 : 256<) were 14 out of 79 adult serums examined (17.7 %).